1971
DOI: 10.1021/je60049a002
|View full text |Cite
|
Sign up to set email alerts
|

PVT properties of liquid n-octane

Abstract: The PYT properties of liquid n-octane are presented for six isotherms: -15.00, 5.00, 25.00, 45.00, 65.00, and 85.00OC. The pressure ranged from atmospheric to near freezing at each temperature. The accuracy is estimated at f0.0006 cm3/cm3. The data were fitted to the Tait equation of state at each temperature. The data were also used to obtain the Tait parameters L and J as functions of temperature. The error introduced by the temperature fitting averaged 0.041 O/O. The worst error introduced was 0.001 7 cm3/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
13

Year Published

1973
1973
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 1 publication
1
11
0
13
Order By: Relevance
“…Triple-distilled water and n-octane (putity >99 mol%, Alfa Chemicals) were used as the reference fluids for claibration. The densities of water were taken from Kell and Whalley [6,7] and those of n-octane from Chappelow et al [8] and Benson and Winnick [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple-distilled water and n-octane (putity >99 mol%, Alfa Chemicals) were used as the reference fluids for claibration. The densities of water were taken from Kell and Whalley [6,7] and those of n-octane from Chappelow et al [8] and Benson and Winnick [9].…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have shown [14,IS] that the Tait equation is probably the best two-parameter equation for accurately representing density data of organic liquids at pressures up to 100 MPa. We have chosen the form of the Tait equation which was used successfully by Winnick and co-workers [9,11] and rewritten in terms of reduced pressure P, and reduced temperature T, as follows: …”
Section: Correlanon Of Pure Component Densitiesmentioning
confidence: 99%
“…Different forms of the Tait equation have been used to represent the PVT behavior for a number of liquids, including polymeric liquids 28, 30–32. The equation used here is: …”
Section: Resultsmentioning
confidence: 99%
“…Τέλος, τα πυκνόμετρα μεταβαλλόμενου όγκου χρησιμοποιούνται για μετρήσεις πυκνό τητας σε πιέσεις μεγαλύτερες της ατμοσφαιρικής. Τέτοια πυκνόμετρα έχουν κατασκευαστεί εδώ και αρκετές δεκαετίες, αρχικά από τον Bridgman [11], Boelhouwer [12], μεταγενέστερα από Q-v f -g ηλεκτρομαγνήτης Εικ.1.2.2 Η ισορροπία δυνάμεων στο πυκνόμετρο μαγνητικού πλωτήρα τους Benson και Winnick [13], ενώ η πιό πρόσφατη κατασκευή αναφέρθηκε από τους Dymond, Isdale και Glen [14]. Το υγρό δείγμα τοποθετείται σε ένα κυλινδρικό κλειστό δοχείο με εύκαμπτα ελατηριοειδή τοιχώματα από ανοξείδωτο χάλυβα (bellow), όπως φαίνεται και στην Εικ.1.2.3, στην πάνω βάση του οποίου είναι κάθετα σταθερά προσαρμοσμένο ένα μεταλ λικό στέλεχος, το επάνω άκρο του οποίου είναι κατασκευασμένο από μαγνητικό υλικό.…”
Section: πειραματικές τεχνικές για την μέτρηση της πυκνότηταςunclassified
“…Για ένα νευτώνειο ρευστό το δυναμικό ιξώδες η είναι η σταθερά αναλογίας που συσχετίζει την διαφορική κλίση της ταχύτητας u με την τάση της διατμήσεως τ που εφαρ μόζεται στην μάζα του ρευστού κατά την κίνηση του και ορίζεται ως εξής CIS]: T=^-(du/dy) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) ενώ το κινηματικό ιξώδες ν ενός ρευστού είναι ο λόγος του απολύτου ιξώδους του προς την πυκνότητα του ν=/7/ρ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) Το ιξώδες διαφέρει από άλλες ιδιότητες που μελετώνται στην εργασία αυτή. Από μα κροσκοπική άποψη είναι μία ιδιότητα "μη ισορροπίας" και χαρακτηρίζει την κίνηση ενός ρευ στού, ενώ η πυκνότητα για παράδειγμα είναι ιδιότητα μιας συγκεκριμένης κατάστασης ισορ ροπίας.…”
Section: το ιξώδες και τεχνικές μέτρησης του 131 ορισμόςunclassified